Dental biofilms contain DNase I-resistant Z-DNA and G-quadruplexes but alternative DNase overcomes this resistance - Evans, Dominique C. S.; Kristensen, Mathilde F.; Minero, Gabriel Antonio S.; Palmén, Lorena G.; Knap, Inge; Tiwari, Manish K.; Schlafer, Sebastian; Meyer, Rikke L. (NPJ biofilms and microbiomes, 2025)
Extracellular DNA (eDNA) in bacterial biofilms can form non-canonical structures like Z-DNA and G-quadruplex (G4), which enhance biofilm resilience by providing protection against mammalian DNases. However, the conformation of eDNA in dental biofilms remains unexplored. Using fluorescence immunolabeling and confocal microscopy, we examined dental biofilms from healthy and caries-active subjects, revealing B-DNA, G4-, and Z-DNA structures surrounding clusters of bacteria, with some structures directly associated with the bacterial cell surface. We demonstrated that these non-canonical DNA structures were resistant to mammalian DNase I. Using a Streptococcus mutans biofilm model, we visualised fluorescently labelled eDNA during enzyme treatment and identified both an experimental nuclease and a DNase I-chloroquine combination capable of removing eDNA that was resistant to DNase I. These findings suggest that G4 and Z-DNA structures represent novel targets for improved enzyme formulations in controlling dental biofilms and potentially other biofilms containing these secondary DNA structures.